The Accountability for Self-Defense (Noodweer) in a Ruling on Assault Resulting in Severe Injury (Case Study of Decision Number 76/Pid.B/2025/PN TJK) - Sidabutar, Bayu; Seftiniara, Intan Nurina; Hartono, Bambang (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study examines criminal liability for self-defense (noodweer) in cases of assault resulting in serious injury, focusing on Decision Number 76/Pid.B/2025/PN TJK. The research analyzes the factors causing the assault within the context of self-defense and the criminal responsibility of defendants who exceed the limits of lawful self-defense. The study employs both normative juridical and empirical approaches, using secondary data such as legislation, criminal law literature, and court decisions, as well as primary data obtained through interviews with investigators, prosecutors, judges, and the defendant. The findings indicate that the assault resulted from a complex interaction of internal and external factors, including emotional instability, economic pressure, an unfavorable environment, a culture of violence, and direct provocation and sudden attacks by the victim. Although the defendant acted under threat, the response was disproportionate and constituted excessive self-defense (noodweer exces). Consequently, the court held the defendant criminally liable under Article 351 paragraph (2) of the Indonesian Criminal Code and imposed a one-year prison sentence. The study emphasizes that lawful self-defense must be proportional and not excessive.